IMPLEMENTATION OF MSME EMPOWERMENT PROGRAMS IN IMPROVING BUSINESS INDEPENDENCE IN DESA CURUGCIUNG, CIKEUSIK DISTRICT, PANDEGLANG REGENCY - Restu Alya Nugraha; Siti Aina Firdaus; Nopi Andayani; Miftah Faiz Ali Ramdhani; Maya Oktaviani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Micro, Small and Medium Enterprises (MSMEs) are crucial for local economic development, employment absorption and community welfare. However, the success of empowerment programmes in rural regions generally stays at the implementation level. This study seeks to examine the implementation of MSME empowerment program in enhancing business independence in Desa Curugciung Kecamatan Cikeusik Kabupaten Pandeglang. The study used a descriptive qualitative design. The collection of data was carried out through observation, semi-structured interviews and documentation with seven informants, including the sub-district head, village head, a BRI officer, the chairperson of the Village Consultative Body, and three MSME actors. Data were evaluated by Miles, Huberman and Saldaña’s interactive approach which consists of data collection, data condensation, data display and conclusion drafting. The findings indicate that the implementation of the MSME empowerment program has not been adequately carried out. Communication on the program at the bureaucratic level was still limited and did not reach the MSME actors to the fullest. Training, mentoring and access to funding were formally provided as resources but not experienced equally by business actors. The commitment of the implementing institutions had not been fully converted into ongoing assistance, while the bureaucratic structure was still more administrative than service-oriented. The results of the study also indicated that the independence of the business of MSME actors is more created via self-initiative, experience and adaptation rather than direct intervention from the empowerment program. The study concluded that the presence of resilient MSMEs in rural areas does not necessarily mean that the policies are well implemented. The essay contributes to the study of public policy implementation in the identification of the gap between the formal empowerment design and the real growth of business independence at the village level.